Relation between light absorption measured by the quantitative filter technique and attenuation of Chlorella fusca cultures of different cell densities: application to estimate the absolute electron transport rate (ETR) - Jerez, Celia G. (2016)
In order to estimate microalgal carbon assimilation or production of Chlorella fusca cultures based on electron transport rate (ETR) as in vivo chlorophyll a fluorescence, it is necessary to determine the photosynthetic yield and the absorbed quanta by measuring the incident irradiance and the fraction of absorbed light, i.e., absorptance or absorption coefficient in the photosynthetic active radiation (PAR) region of the spectra. Due to difficulties associated with the determination of light absorption, ETR is commonly expressed as relative units (rETR) although this is not a good estimator of the photosynthetic production since photobiological responses depend on the absorbed light. The quantitative filter technique (QFT) is commonly used to measure the absorbed quanta of cells retained on a filter (AbQf) as estimator of the absorbed quanta of cell suspensions (AbQs) determined by using integrating spheres. In this study, light attenuation of thin-layer cell suspensions is determined by using a measuring system designed to reduce the scattering. The light attenuation is related to the absorptance as the fraction of absorbed light by both indoor and outdoor C. fusca cultures of different cell densities. A linear relation between AbQf and AbQs (R2 = 0.9902, p < 0.01) was observed, AbQf = 1.98 × AbQs, being 1.98 an amplification factor to convert AbQs values into AbQf ones. On the other hand, depending on the culture system, the convenience of the use of the absorptance, light absorption or specific light absorption coefficient expressed per area (thin-layer cascade or flat panel cultivators), volume (cylindrical and tubular photobioreactors), or chlorophyll units (any type of cultivation system) is discussed. The procedure for the measurement of light absorption presented in this study for C. fusca could be applied in other phytoplankton groups. The absorbed quanta as determined in this study can be used to express absolute ETR instead of relative ETR, since the first one provides much more relevant photobiological information of microalgae culture systems.